The Ability to Compose Academic Writing of the Sixth Semester Students of English Department Universitas PGRI Semarang in the Academic Year 2021-2022 - Wibowo, Amin (Universitas PGRI Semarang, 2022)
This study investigates the ability of the sixth semester students of the English Department of PGRI Semarang University to compose academic writing. The main objective of this study is to find out the ability in composing academic writing of the sixth semester students of the English Department of PGRI Semarang University in the academic year 2021-2022. The writer used the descriptive quantitative method. The total number of the sixth semester regular students is 283 students, so the total number of the population is 283 thesis proposals. Methodology is a set of methods used in a particular area of activities (Hornby, 1995, p. 734). Methodology of the research here means a set of methods used to investigate the objectives of the study. There are seven main parts discussed in this chapter. Those are type of the research, subject of the study, instrument of the research, technique of data collection, and technique of data analysis. The figure of 70,2 is in the range of 66 – 79 which is categorized into good. Therefore, it can be concluded that the ability of the sixth semester students of the English Department of PGRI Semarang University in the academic year 2021-2022 in composing academic writing is good.